2019
DOI: 10.1016/j.theriogenology.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Activin promotes growth and antral cavity expansion in the dog ovarian follicle

Abstract: Understanding regulators of folliculogenesis remains limited in the domestic dog (Canis familiaris), which challenges our ability to develop in vitro follicle culture systems for canid genome rescue efforts. Here, we investigated the influence of activin on dog follicle development and survival, oocyte quality, and FSH receptor expression in culture. Preantral (150-≤230 µm diameter), early antral (231-≤330 µm), and antral (>330-550 µm) stage follicles were encapsulated in a fibrin-alginate hydrogel with 0, 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 67 publications
2
14
0
3
Order By: Relevance
“…The FSH-dependent pathways are also regulated by the members of the transforming growth factor β (TGF-β) family, including activins, inhibins, and anti-Müllerian hormone (AMH). Activins increase the FSH receptor expression and enhance the stimulatory effects of FSH on ovarian steroidogenesis [ 262 , 263 ]. In contrast, AMH and inhibins suppress the stimulatory effects of FSH on folliculogenesis [ 249 , 262 , 264 , 265 ].…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…The FSH-dependent pathways are also regulated by the members of the transforming growth factor β (TGF-β) family, including activins, inhibins, and anti-Müllerian hormone (AMH). Activins increase the FSH receptor expression and enhance the stimulatory effects of FSH on ovarian steroidogenesis [ 262 , 263 ]. In contrast, AMH and inhibins suppress the stimulatory effects of FSH on folliculogenesis [ 249 , 262 , 264 , 265 ].…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…Mouse pre-antral follicles secrete activin A which, in turn, stimulates granulosa cell proliferation and follicle growth (Bloise et al, 2019). Activin We recently demonstrated that activin A acts synergistically with FSH to support in vitro growth of dog antral follicles during 21-day in vitro culture (Nagashima, Wildt, Travis, & Songsasen, 2019). Furthermore, activin and FSH promote antral cavity expansion in vitro in early and antral follicles but do not support the transition of the pre-antral to antral stage (Nagashima et al, 2019).…”
Section: Activinmentioning
confidence: 99%
“…Activin We recently demonstrated that activin A acts synergistically with FSH to support in vitro growth of dog antral follicles during 21-day in vitro culture (Nagashima, Wildt, Travis, & Songsasen, 2019). Furthermore, activin and FSH promote antral cavity expansion in vitro in early and antral follicles but do not support the transition of the pre-antral to antral stage (Nagashima et al, 2019). Finally, activin supports in vitro growth and viability of dog oocytes by sustaining bidirectional communication between the gamete and somatic cells during the 21-day culture (Nagashima et al, 2019).…”
Section: Activinmentioning
confidence: 99%
See 2 more Smart Citations